1997
DOI: 10.1002/pro.5560061208
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of temperature factor distribution in high‐resolution protein structures

Abstract: The temperature factors obtained from X-ray refinement of proteins at high resolution show large variations from one structure to another. However, the B-values expressed in units of standard deviation about their mean value @'-factor) at the Ccu atoms show remarkably characteristic frequency distribution. In all of the 1 I O proteins examined in this study, the frequency distribution exhibited a bimodal distribution. The peaks in the B'-factor frequency distribution occur at -1.1 and 0.4 for a bin size of 0.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(66 citation statements)
references
References 20 publications
(10 reference statements)
1
64
0
1
Order By: Relevance
“…Waters with higher burial terms (near one) tended to have lower B-factors. These results are similar to those of Parthasarathy and Murthy, 72 who found that buried protein residues have low B-factors while exposed ones have high Bfactors. The entropy might be expected to correlate better with the B-factors than the burial, since one can imagine at least two types of fully buried waters, those that can satisfy optimal hydrogen bonds in only one orientation and those that can make similar interactions with the protein/ligand system in a number of different orientations.…”
Section: Relating Szmap-calculated Properties and Experimental B-factsupporting
confidence: 93%
“…Waters with higher burial terms (near one) tended to have lower B-factors. These results are similar to those of Parthasarathy and Murthy, 72 who found that buried protein residues have low B-factors while exposed ones have high Bfactors. The entropy might be expected to correlate better with the B-factors than the burial, since one can imagine at least two types of fully buried waters, those that can satisfy optimal hydrogen bonds in only one orientation and those that can make similar interactions with the protein/ligand system in a number of different orientations.…”
Section: Relating Szmap-calculated Properties and Experimental B-factsupporting
confidence: 93%
“…In order to better investigate the significance of the B-factor variation along the single chains and to better compare different structures, we have normalised the B-factors (introducing the socalled B 0 -factors) in terms of unit of standard deviation about their mean value: B 0 ¼ ðB À hBiÞ=rðBÞ (Parthasarathy and Murthy, 1997;Yuan et al, 2003Yuan et al, , 2005. The B 0 -factor profiles for different chains are homogeneous within the same pH (8.5 and 6.5) and, at pH 6.5, within the same chain type (A and B), i.e.…”
Section: Resultsmentioning
confidence: 99%
“…ported on analysis of the observed B-factor values from protein crystals. [9][10][11] These works revealed large information about the dynamic behavior of protein structures. It was found that, for example, hydrophobic residues, which are usually buried in protein interiors, tend to be more rigid, whereas charged and polar residues standing on protein surfaces are prone to be more flexible.…”
Section: Introductionmentioning
confidence: 99%